Consumption Practices Based on the Dimension of Religiosity: A Study of Urban and Suburban Communities - Habibi, Ahmad; Mukri, Moh.; Normasyhuri, Khavid; Abidin , Noor Azliza Zainal (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines differences in food consumption behaviors between urban and suburban communities in Lampung Province, Indonesia, particularly in relation to religiosity. Employing a quantitative comparative framework, the research analyzes consumption patterns through four dimensions of religiosity: beliefs, knowledge, practices, and behaviors. Primary data were collected from 250 respondents in urban environments within Indonesia’s Bandar Lampung City and suburban areas in South Lampung Regency using purposive sampling. Data were gathered via Google Forms and evaluated using a Likert Scale. The findings indicate no significant differences between urban and suburban residents regarding consumption behaviors related to religious beliefs and practices. However, notable variations exist in knowledge and behavior dimensions, suggesting that urban and suburban contexts shape food choices differently under religious influences. The study highlights the need for policymakers and businesses to consider religious factors when promoting sustainable consumption. It argues that urbanization and access to religious education play crucial roles in shaping food consumption choices influenced by religiosity.